Belief in God: Why People Believe, and Why They Don't. (August 2018) - Mercier, Brett; Kramer, Stephanie R.; Shariff, Azim F.
Belief in a god or gods is a central feature in the lives of billions of people and a topic of perennial interest within psychology. However, research over the past half decade has achieved a new level of understanding regarding both the ultimate and proximate causes of belief in God. Ultimate causes—the evolutionary influences on a trait—shed light on the adaptive value of belief in God and the reasons why a tendency toward this belief exists in humans. Proximate causes—the immediate influences on the expression of a trait—explain variation and changes in belief. We review this research and discuss remaining barriers to a fuller understanding of belief in God.